한옥의 친환경 특성이 인간에게 미치는 영향요소 분석 - 안의종(Ahn Uijong) (KIEAE Journal, 2014)
The beauty of Korean architecture is in its natural beauty. Traditional residence of Korea is architecture that expresses modesty that is embraces the nature. Hanok is designed based on understanding of the nature and responding to it. For this reason, Hanok is a nature-friendly residential space. There are many unique traits of Hanok and one of them is that it is built based on scientific principles. Hanok, without using modern technology and machines, utilizes effectively the natural environment and the climate, e.g., the sun and the wind. Hanok, based on Korea's geographical condition and climate characteristics, have produced a variety of residential houses. The principle of Hanok is not to challenge the nature but embrace and accept it. Furthermore, in Hanok is embedded Korea's traditional philosophy and ideas and it is not simply a simple residential space but also a place for meditation and spiritual training. As the time passes, there are more researches are being done to enhance health in addition to traditional role of protection and convenience. Accordingly, more efforts are being made to bring the nature into human life. Hanok, the traditional residential form of Korea, has environment-friendly architecture and characteristics that could promote human health and enhance our life. Therefore, the nature-oriented philosophy and environmental elements of Hanok should be more systematically studied to take advantage of its architectural advantages and create healthier modern residential culture.